The Regency Government's Efforts in the Complete Systematic Land Registration Program - Perdana, Valent Dika Wahyu; Rodhiyah, Siti (Jurnal Konstatering, 2022)
The speed of Complete Systematic Land Registration Program (PTSL) prioritizes the smooth running of the process, but without neglecting the precision and thoroughness, prudence and accuracy in handling it. This study aims to: 1) Know and analyze the efforts of the Jepara Regency Government in the Complete Systematic Land Registration program at the Jepara Regency Land Office 2) Know and analyze the obstacles faced by the Jepara Regency Government in carrying out the Complete Systematic Land Registration program at the Jepara Regency Land Office 3) Know and analyze how to overcome these obstacles in the implementation of the Complete Systematic Land Registration program at the Jepara District Land Office. The legal research used is an empirical legal research approach. The specification of the research used is analytical descriptive in nature, namely research that describes legal phenomena, describes in a factual and accurate systematic manner the government's efforts to realize a certified land program for the people in the work area of the Jepara Regency Land Office and provides an assessment of the results of the description without intending to provide conclusions that are general. The results of the research and discussion show that the Jepara Regency Government's efforts in the Complete Systematic Land Registration program at the Jepara Regency Land Office are by carrying out the Complete Certificate Land Registration (PTSL) program in every sub-district in Jepara Regency.Keywords :Â  Effort; Government; Systematic.